Экологическая обусловленность сердечной деятельности у Mustelidae - Терновский, Д.В.; Туманов, И.Л.; Терновская, Ю.Г. (Вестник зоологии, 1981)
Studies in the bioelectrical cardiac activity, respiration act and body temperature of mustelids permitted species specific properties of these animals to be revealed, which contributes to comprehension of their adaptation mechanisms. The data of the research make it possible to differentiate the species by the level of the physiological activity, which may be of essential significance when specifying their taxonomic belonging.